Assessment of intracranial meningioma‐associated calcifications using susceptibility‐weighted MRI. Issue 4 (20th January 2017) - Adams, Lisa C.; Böker, Sarah M.; Bender, Yvonne Y.; Fallenberg, Eva M.; Wagner, Moritz; Buchert, Ralph; Hamm, Bernd; Makowski, Marcus R.
Abstract : Purpose: To determine the diagnostic accuracy of susceptibility‐weighted MRI (SW‐MRI) for the detection of intracranial meningioma‐associated calcifications compared with standard MR sequences, using computed tomography (CT) as a reference standard. Materials and Methods: 354 patients, who had received both a CT and a 1.5 Tesla clinical brain MRI with SW‐MRI sequences between January 2014 and July 2016, were retrospectively evaluated and 316 patients were included. Calcification diameter was used to assess correlation between imaging modalities. Sensitivity and specificity as well as intra‐ and interobserver agreement were calculated for SW‐MRI and standard MRI sequences when compared with reference standard CT. Results: Fifty patients had positive findings for intracranial meningioma‐associated calcifications on CT scans. SW‐MRI reached a sensitivity of 94% (95% confidence interval [CI]: 83–99%) and a specificity of 95% (95% CI: 92–98%) for the detection of meningioma‐associated calcifications, while standard MRI yielded a sensitivity of 64% (95% CI: 49–77%) and a specificity of 94% (95% CI: 90–96%). Diameter measurements between SW‐MRI and CT showed a close correlation (R 2  = 0.99; P  < 0.001) with a slight overestimation of size, which, however, did not reach significance level (SW‐MRI: 8.2 mm ± 7.1; CT: 6.8 mm ± 6.4; P  = 0.29). Compared with standard MRI, SW‐MRI showed a better interobserver agreement for size measurements of calcifications. Conclusion: SW‐MRI enables a reliable detection of intracranial meningioma‐associated calcifications by using CT as a reference and offers a higher diagnostic accuracy than standard MRI. Level of Evidence: 3 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2017;46:1177–1186.